Investigating microglial and neuronal cellular responses to alpha-synuclein preformed fibril and adeno-associated viral vector delivery to the rat substantia nigra and to primary cortical rat cell cultures - Tyndall, Caoimhe Orlaith (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2025)
Intracytoplasmic accumulation of the alpha-synuclein (Syn) protein in the brain is a pathogenic hallmark of Parkinsons disease and other synucleinopathic diseases. In the diseased brain, Syn exploits its innate ability to recruit nave monomers for nucleation, polymerisation, and elongation into larger order polymers of fibrillar structure. Syn fibrils obstruct physiological cellular processing by propagating throughout neuronal networks and aggregating intracellularly into proteinaceous inclusions called Lewy bodies. Prior to Lewy body accumulation and neuronal dysfunction, fibrillar Syn triggers chronic microglial activation and production of pro-inflammatory cytokines, which inflict cytotoxic damage to vulnerable neuronal populations. The A53T mutation, an autosomal dominant point mutation in the gene encoding Syn, is thought to accelerate the capacity for Syn to fibrillise, and to promote microglial activation towards a pro-inflammatory phenotype in the brain. Activation of the glial expressed beta2 adrenergic receptor (2AR) drives anti-inflammatory signalling in the brain, conferring protection against neurodegeneration associated with microglial activation. As such, pharmacologically targeting 2ARs may prove efficacious in alleviating Syn-induced inflammation and neurodegeneration observed in patients with synucleinopathy. Development of clinically relevant animal models of synucleinopathy are warranted to provide a means to assess mechanisms of Syn-associated microglial activation and neurodegeneration, and to evaluate the potential of combative treatment strategies targeting underlying disease mechanisms. The present investigation involves the development of a novel rat model of synucleinopathy, comprising unilateral intranigral fibrillar deposition and genetic overexpression of Syn to drive microglial activation, neurodegeneration, and motor dysfunction representative of neuropathology observed in human synucleinopathic conditions. Unilateral stereotactic delivery of A53T-mutant human recombinant Syn preformed fibrils (PFF), in combination with adeno-associated viral (AAV) vector mediated expression of A53T-mutant human Syn, into the substantia nigra, induced phosphorylation of endogenous rat Syn, stimulated microglial activation, and reduced dopaminergic neuronal cell bodies in the substantia nigra ipsilateral to the injection. Cellular changes were coupled with reduced contralateral limb-use, six weeks post-delivery. Treatment with the long acting and brain penetrable 2AR agonist formoterol, previously reported to reduce microglial activation in an inflammatory rat model of Parkinsons disease, proved ineffective in altering the distribution of phosphorylated Syn or prominence of microglial reactivity. Formoterol treatment appeared to mitigate the unilateral loss of nigral dopaminergic neuronal cell bodies, and partially alleviate motor behavioural changes associated with intranigral A53T PFF+AAV. These results suggest a possible neuroprotective role for 2AR activation in synucleinopathic conditions. Further experiments, which assessed Syn-induced changes in rat primary microglial cultures, and related changes in neuronal complexity following the transfer of glial conditioned media to primary neuronal cultures, were inconclusive regarding the possible underlying Syn-associated glial-neuronal interactions contributing to mechanisms of neurodegeneration. Treatment of mixed and enriched microglial cultures with Syn PFFs failed to trigger microglial activation, or glial-associated changes in neuronal complexity. These outcomes highlighted the limitations of the present in vitro approaches for modelling glial-neuronal interactions in neurodegenerative disease states, and/or evaluating the potential of pharmacological agents for disease modifying approaches. Further research is required to optimise models and to elucidate glial-neuronal interactions underlying neurodegeneration in synucleinopathic diseases.
APPROVED
Keywords: Microglia; Parkinson's disease; Alpha-synuclein; Noradrenaline; Beta-2-adrenoceptor; Neurodegeneration; Neuroinflammation